RECYCLING OPPORTUNITIES FOR TEXTILE WASTE IN LATVIA - Lupkina, Laine; Noviks, Gotfrīds; Kriipsalu, Mait (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Textile industry is experiencing rapid growth due to changing consumer and fashion patterns. For example, in 2015, EU citizens bought about 12.66 kg of textile items per person. This generates a large amount of textile waste every year, making impact on environment and human health. Therefore, targets in European Union and national level are being set to reduce the amount of textile waste going to landfill. To achieve them, it is necessary to recycle textile waste into new products. The aim of the article is to research possible solutions for textile waste recycling, including the example of Estonia, as well as to create an engineering solution for textile waste recycling in Latvia to achieve goals of Directive (EU) 2018/851.